Migration and educational aspirations: Another channel of brain gain? - Marcus H. Böhme (IZA Journal of Migration, 2015)
International migration not only enables individuals to earn higher wages but also exposes them to new environments. The norms and values experienced in destination countries can change the behavior of migrants and also of family members left behind. This paper suggests that brain gain can take place due to a change in the educational aspirations of caregivers in migrant households. Estimates for Moldova show that international migration raises parental aspirations in households located at the lower end of the human capital distribution. The identification of these effects relies on GDP growth shocks in the destination countries and migration networks. These results imply that aspirations are a highly relevant determinant of intergenerational human capital transfer and that even temporary international migration can shift human capital formation to a higher steady state by inducing higher educational aspirations among caregivers.
Keywords: D03; O12; I21; J61; 330; Education; Aspirations; Migration; Brain gain